2002
DOI: 10.1177/030089160208800508
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Invasive Bladder Cancer in Elderly-Unfit Patients with Concomitant Illness: Can a Curative Radiation Therapy be Delivered?

Abstract: Elderly-unfit patients with comorbidities and >70 years of age can be submitted to radical pelvic irradiation. The results observed in this retrospective analysis have encouraged us to use non-palliative radiotherapy doses in these patients with muscle-invasive bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Patients with many mild comorbidities or several severe comorbidities can have a poor treatment outcome even though they may otherwise have good KPS. Data observed in our patients seem to confirm the feasibility of curative treatment in patients with high Charlson score value such as observed in other articles (14)(15)(16)(17)(18)(19). In fact, our patients tolerated the treatment well although they had many illnesses with a median CCI score of 6.5.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with many mild comorbidities or several severe comorbidities can have a poor treatment outcome even though they may otherwise have good KPS. Data observed in our patients seem to confirm the feasibility of curative treatment in patients with high Charlson score value such as observed in other articles (14)(15)(16)(17)(18)(19). In fact, our patients tolerated the treatment well although they had many illnesses with a median CCI score of 6.5.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, Sengelov and coworkers [31] confirmed that curative intended radiotherapy is feasible in elderly patients, with 29% surviving for 2 years. The overall actuarial median survival under 2DRT techniques in these reports ranged from 9 to 21.5 months [30,32,33]. In our institute, the median survival is 21 months.…”
Section: Discussionmentioning
confidence: 92%
“…For elderly patients with locally advanced bladder cancer, several reports concluded that RT also was an effective treatment option for elderly patients who were not suitable for cystectomy. Santacaterina et al [30] reported that elderly patients with muscle-invasive bladder cancer who underwent RT had a median survival of 21.5 months. Additionally, Sengelov and coworkers [31] confirmed that curative intended radiotherapy is feasible in elderly patients, with 29% surviving for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 45 unfit patients were treated with radiation fields encompassing bladder and grossly involved lymph-nodes. Treatment was considered safe and achieved a 3- and 5-year OS of 36% and 19.5%, respectively; with a median survival of 21.5 months ( 50 ). A recent study reported similar results but included patients with T1 to T4 BCa, making difficult to compare this population to MIBC patients.…”
Section: Evidence Synthesismentioning
confidence: 99%